The protection of minority rights in sri lanka a criticalanalysis of the role of the judici - Kosalai, M. (University of Jaffna, 2016)
The rights of the minorities; Tamils, Muslims and Indian origin Tamils have not been protected in many instances in Sri Lanka. The paper attempts to explore the role of the judiciary in protecting the rights of the minorities and how it responded to it in the post - independence era. There are plenty of cases ranging from the Mudanayake case, showcase the failure on the part of the judiciary to positively respond to the claims of the minorities. The researcher has analysed the manner in which the judiciary approached and determined the minority claims and the factors if any which prevented the judiciary from actively engaged in the process. The judiciary in a multi ethnic country like Sri Lanka, has the responsibility to protect the interests of the minorities which is a sina qua non for the nation building process. Nonetheless the failure to adopt sensitive approach, and the inability to superintend the functions of the other organs, has significantly impacted in causing deeply divided societies in Sri Lanka. The research is a qualitative study. The provisions of the successive Constitutions, legislations, research papers and relevant cases are critically analyzed. Kishali Pinto Jayawardena and Jayantha De Almeda Gunaratne are interviewed as they possess sound knowledge in dealing with the cases involving minority rights and have engaged in a series of research on the topic. It is worthy to understand the role of the judiciary in protecting the minority interests in the time when the state has committed to building up the nation through the reform of the present Constitution.
Keywords: Contribution; Minorities; Protection judiciary; Rights